Role of TG2-Mediated SERCA2 Serotonylation on Hypoxic Pulmonary Vein Remodeling - Liu, Bo; Wang, Dong; Luo, Erfei; Hou, Jiantong; Qiao, Yong; Yan, Gaoliang; Wang, Qingjie; Tang, Chengchun (Frontiers in Pharmacology, 2020)
Sarco endoplasmic reticulum Ca2+ ATPase (SERCA) pumps take up Ca2+ from the cytoplasm to maintain the balance of intracellular Ca2+. SERCA2 is a key modulator of calcium cycling in both cardiomyocytes and vascular smooth muscle cells (SMCs). This study aimed to investigate the role of transglutaminases2 (TG2) as a key factor involved in SERCA2 serotonination (s-SERCA2) and to elucidate the underlying mechanism of action. Human pulmonary venous smooth muscle cell in normal pulmonary lobe were isolated and cultured in vitro. Establishment of hypoxic pulmonary hypertension model in wild type and TG2 knockout mice. SERCA2 serotonylation was analyzed by co-IP When the TG2 gene silenced or overexpressed under normoxia and hypoxia in vivo and vitro. Intracellular calcium ion was measured by using Fluo-4AM probe under normoxia and hypoxia. RT-PCR and Western Blot analyzed expression of TG2, TRPC1 and TRPC6 under normoxia and hypoxia. We conﬁrmed that 1) hypoxia enhanced the expression and activity of TG2, and 2) hypoxia increased the basal intracellular Ca2+ concentration([Ca2+]i) and SOCE through activating TRPC6 on human pulmonary vein smooth muscle cells (hPVSMC). Then, we investigated the effects of overexpression and downregulation of the TG2 gene on the activity of SERCA2, s-SERCA2, basal [Ca2+]i, and SOCE under normoxia and hypoxia in vitro, and investigated the activity of SERCA2 and s-SERCA2 in vivo, respectively. We confirmed that SERCA2 serotonylation inhibited the activity of SERCA2 and increased the Ca2+ influx, and that hypoxia induced TG2-mediated SERCA2 serotonylation both in vivo and in vitro. Furthermore, we investigated the effect of TG2 activity on the biological behavior of hPVSMC by using an inhibitor and agonist of SERCA2, respectively. Finally, we conﬁrmed that chronic hypoxia cannot increase vessel wall thickness, the right ventricular systolic pressure(RVSP) and right ventricular hypertrophy index(RVHI) of vascular smooth muscle-specific Tgm2-/- mice. These results indicated that hypoxia promoted TG2-mediated SERCA2 serotonylation, thereby leading to inhibition of SERCA2 activity, which further increased the calcium influx through the TRPC6 channel. Furthermore, tissue-specific conditional TG2 knockout mice prevents the development of pulmonary hypertension caused by hypoxia. In summary, we uncovered a new target(TG2) for treatment of chronic hypoxic pulmonary hypertension (CHPH).